Effects Of Janani Suraksha Yojana (A Maternity Benefit Scheme) Up-On the Utilization of Ante-Natal Care Services in Rural & Urban-Slum Communities of Dehradun - Sharma, Parul; Kishore, Surekha; Gupta, Sanjeev K; Semwal, Jayanti (National Journal of Community Medicine, 2012)
Background: Janani Suraksha Yojana (JSY) –a new maternity benefit scheme - was launched by Govt. of India in April 2005 with the objective of reducing maternal and neonatal mortality by promoting institutional deliveries by providing cash incentive to beneficiaries as well as promoter. Ante –natal services are one of the most important component of JSY. Study was designed to assess the ante-natal characteristic of JSY beneficiaries. Materials and Methods: A cross-sectional study was conducted under rural health training centre and urban health training centre of the field practice area of department of Community Medicine, HIMS, Dehradun. Results: A total of 2221 married women (15-49 years) were interviewed out of which 1290(58.08%) women were from urban slums and 931(41.92%) women belonged to rural areas. Out of the total number of married women who delivered at govt. hospital i.e. 227 (75.17%), majority (78.42%) of the women were registered with the some health personals. Out of these, 74.15% women were registered with ASHA .Only 29.21% women went for three or more ANC visits. Only 48.31% women consumed hundred IFA tablets and the proportion was high (79.41%) in rural women. All the women received complete TT immunization. Conclusion: It was found that registration of the women with some health personnel was influenced by women’s religion and socio-economic status the level of education and socio-economic status was found to have a positive effect on the number of ANC visits. The consumption of IFA tablets was also found to be influenced by the educational status of the women.